Ruthenium sensitizers with various 2-thiophenimidazo[4, 5-f][1, 10]phenanthroline based ancillary ligands and their performance for dye-sensitized solar cells. (June 2015) - Ma, Bin-Bin; Peng, Yu-Xin; Tao, Tao; Geng, Jiao; Huang, Wei
Abstract: This paper reports four new ruthenium sensitizers (S1 –S4 ) for the studies on dye-sensitized solar cells. The four ruthenium sensitizers have been synthesized via a step-by-step synthetic strategy via their respective precursors (D1 –D4 ), where 2-thiophenimidazo[4, 5- f ][1, 10]phenanthroline based ancillary ligands are present with different substituents at α and β positions of the thiophene unit. It is found that the introduction of an electron-deficient radical at β positions of the thiophene unit in the ancillary ligand has a positive influence on the efficiency of the final dye-sensitized solar cells, where sensitizerS3 shows the best overall power-conversion efficiencies in this group of ruthenium sensitizers (4.95% compared to 6.07% for sensitizer N3). In addition, three single-crystal structures of organometallic precursors (D1 –D3 ) are included, which are the first structural examples on Ru(II) complexes containing p -cymene and TIP based ligands simultaneously. Graphical abstract: We report the design and synthesis of four new ruthenium sensitizers (S1 –S4) with different TIP based ancillary ligands including an isomeric pair (S2 andS3 ), where different substituents in the ancillary ligands have a remarkable influence on the final PCES of the DSCs. Highlights: Four heteroleptic Ru(II) TIP based sensitizers (S1 –S4 ) are described. S3 shows much better PCEs than its isomeric complexS2 . α or β substituent of the thiophene ring affects greatly the device performance. Three of four precursors (D1 –D3 ) are firstly revealed by single-crystal structures.